Penerapan Model Project Based Learning dengan Media Tiga Dimensi Terhadap Kreativitas Siswa pada Materi Sistem Pencernaan Manusia Kelas VIII di MTsN 3 Banda aceh - Eriawati; Nafisah Hanim; Mahdalena (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This research is motivated by the lack of use of media and the application of learning models that are in accordance with learning materials in class VIII MTsN 3 Banda Aceh, resulting in a lack of student creativity when learning, therefore it is necessary to apply cooperative-based learning models such as the Project Based Learning model. This study aims to analyze student creativity using the Project Based Learning model with three-dimensional media on the material on the Human Digestive System in class VIII at MTsN 3 Banda Aceh. The sample used in this study was class VIII-3 students of 21 students. Data collection was carried out using project assessment sheets. The results of the analysis show that the average percentage of student group creativity in learning is 89% with very creative criteria. So it can be concluded that the application of the Project Based learning model with three-dimensional media can make students' creativity very creative.